Sistem Pendukung Keputusan Penentuan Beasiswa Menggunakan Metode SAW - M. Noer Iskandar Nuriz Ansori; Sunardi Sunardi; Taufik Saleh (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2023)
This research aims to design and develop a decision support system for selecting high-achieving students using the Simple Additive Weighting (SAW) method at SMP Miftahul Ulum. The system is designed as a web-based application using PHP programming language and data storage using MySQL. Currently, the selection of high-achieving students at mts at taqwa is still done manually using Microsoft Excel, which is time-consuming and prone to errors. Therefore, this research utilizes the SAW method as an approach to decision-making. The SAW method allows the assessment of students based on predetermined criteria and preference weights, enabling objective and measurable evaluations. The decision support system developed in this research assists the school in determining high-achieving students based on established criteria. With this system, it is expected that the school can improve efficiency and accuracy in assessing high-achieving students. The system also aids in storing and processing student data effectively. This research has practical benefits in enhancing the quality of assessing high-achieving students at mts at taqwa The developed decision support system provides accurate and reliable information regarding decision-making calculations. Thus, this research can serve as a reference for other schools in developing similar systems. Keywords Decision support system, high-achieving students, Simple Additive Weighting (SAW), web-based application, student assessment.